2012
DOI: 10.1021/ml300197h
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeptidic Lysosomal Modulators Derived from Z-Phe-Ala-Diazomethylketone for Treating Protein Accumulation Diseases

Abstract: Lysosomes are involved in protein turnover and removing misfolded species, and their enzymes have the potential to offset the defect in proteolytic clearance that contributes to the age-related dementia Alzheimer's disease (AD). The weak cathepsin B and L inhibitor Z-Phe-Ala-diazomethylketone (PADK) enhances lysosomal cathepsin levels at low concentrations, thereby eliciting protective clearance of PHF-τ and Aβ42 in the hippocampus and other brain regions. Here, a class of positive modulators is established wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Note Added in Proof-A recent paper by K. Viswanathan et al (33) identified new cathepsin B-enhancing small molecules that protect against synaptic deficits in a transgenic model of AD.…”
Section: Acknowledgments-we Thank Drs Hidde Ploegh and Christoph Petmentioning
confidence: 99%
“…Note Added in Proof-A recent paper by K. Viswanathan et al (33) identified new cathepsin B-enhancing small molecules that protect against synaptic deficits in a transgenic model of AD.…”
Section: Acknowledgments-we Thank Drs Hidde Ploegh and Christoph Petmentioning
confidence: 99%
“…Note that the positive modulation of CatB by E64d was less pronounced than the enhancing effect produced by PADK (increase of 76% vs. 549%; p<0.001). Other weak cysteine protease inhibitors were also found to up-regulate active CatB to varying degrees, including i ) SD1002, a non-peptidyl PADK analogue previously found to promote Aβ 42 clearance (Viswanathan et al, 2012), ii ) the polyphenol quercetin that, like PADK and E64d, exhibits very weak CatB inhibitory action (Ramalho et al, 2015), and iii ) Cathepsin Inhibitor 1 (CATI-1, also known as Z-Phe-Gly-NHO-Bz), a broad inhibitor of papain and several cathepsins (Table 2). The potent CatB inhibitors CA074, CA074me, and E64 did not exhibit positive modulation of CatB-30.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, a growing number of studies has investigated agents that enhance enzymes appropriately involved in protein clearance. The CatB cysteine protease is one such enzyme: it is a lysosomal hydrolase that degrades Aβ into less amyloidogenic species (Mueller-Steiner et al, 2006; Butler et al, 2011; Wang et al, 2012; Cermak et al, 2016; Park et al, 2016) and it is neuroprotective when up-regulated, reducing synaptic and behavioral deficits related to AD (Mueller-Steiner et al, 2006; Sun et al, 2008; Butler et al, 2011; Yang et al, 2011; Viswanathan et al, 2012). The PADK and E64d compounds compared here are both very weak inhibitors of the Aβ-degrading CatB, but both were found to up-regulate CatB levels which may explain their beneficial actions in AD mouse models (see Butler et al, 2011; Hook et al, 2011; Bahr et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, enhancing the autophagy-lysosomal pathway of protein clearance is becoming widely accepted as a plausible treatment avenue for many indications, including CNS, metabolic, inflammatory, infectious, and muscle disorders [5][6][7][8][9][10]. Regarding the treatment of multi-proteinopathy, small-molecule cathepsin B modulators not only reduce intracellular Aβ, and consequently extracellular Aβ levels, they also reduce pathogenic forms of tau, and for both Aβ and tau, their enhanced clearance was associated with recovery of synaptic proteins [11,12]. In addition, an 18-residue peptide that promotesthe lysosomal degradation pathway of autophagy was found to enhance clearance of polyglutamine aggregates related to Huntington's disease [13].…”
Section: Introductionmentioning
confidence: 99%